Low-Frequency Mechanical Stimulation Modulates Osteogenic Differentiation of C2C12 Cells. (19th February 2013) - Khayat, Ghazaleh; Rosenzweig, Derek H.; Khavandgar, Zohreh; Li, Jingjing; Murshed, Monzur; Quinn, Thomas M.
Abstract : Mechanical stimulation influences stem cell differentiation and may therefore provide improved lineage specification control for clinical applications. Low-frequency oscillatory mechanical stimulation (0.01 Hz) has recently been shown to suppress adipogenic differentiation of mesenchymal stem cells, indicating that the range of effective stimulation frequencies is not limited to those associated with locomotion, circulation, and respiration. We hypothesized that low-frequency mechanical stimulation (0.01 Hz) can also promote osteogenic cell differentiation of myoblastic C2C12 cells in combination with BMP-2. Results indicate that low-frequency mechanical stimulation can significantly enhance osteogenic gene expression, provided that differentiation is initiated by a priming period involving BMP-2 alone. Subsequent application of low-frequency mechanical stimulation appears to act synergistically with continued BMP-2 exposure to promote osteogenic differentiation of C2C12 cells and can even partially compensate for the removal of BMP-2. These effects may be mediated by the ERK and Wnt signalling pathways. Osteogenic induction of C2C12 cells by low-frequency mechanical stimulation is therefore critically dependent upon previous exposure to growth factors, and the timing of superimposed BMP-2 and mechanical stimuli can sensitively influence osteogenesis. These insights may provide a technically simple means for control of stem cell differentiation in cell-based therapies, particularly for the enhancement of differentiation toward desired lineages.